A genomic-library based discovery of a novel, possibly synthetic, acid-tolerance mechanismin Clostridium acetobutylicum involving non-coding RNAs and ribosomal RNA processing - Borden, Jacob R. (2010)
We generated a genomic library from sheared Clostridium acetobutylicum 824 DNA, whereby inserts can be expressed in both directions from the thiolase promoter, P(thl). Serial transfer of library-bearing C. acetobutylicum cultures exposed to increasing butyrate concentrations enriched for inserts containing fragments of rRNA genetic loci. The selected library inserts were placed so that antisense (to the rRNAs) non-coding RNAs (ncRNAs) would be transcribed from P(thl). Different enriched inserts imparted similar butyrate-tolerance characteristics. A minimal tolerance fragment (RDNA7) was identified as the 16S-rRNA promoter region. Expressed on plasmid pRD7 off P(thl), RDNA7 can produce putative ncRNAs termed ncRNA(RD7). C. acetobutylicum 824(pRD7) showed superior resistance to butyrate and other carboxylic acids. Transcriptional analysis of butyrate stress identified 120 differentially expressed genes between 824(pRD7) and 824(pSOS95del). The few upregulated genes included the ffh gene of the putative signal recognition particle (SRP) system. Northern analysis of ncRNA(RD7) and corresponding antisense RNAs demonstrated multiple ncRNA(RD7) molecules in 824(pRD7). Several corresponding antisense RNA molecules were identified both in 824(pRD7) and 824(pSOS95del), but at much higher levels in 824(pRD7). Northern analysis of 16S rRNA expression suggested complex RDNA7-dependent rRNA processing. Our data suggest that by hybridizing against unprocessed rRNA precursors, ncRNA(RD7) alters rRNA processing, and these alterations result in acid tolerance, possibly through a mechanism involving the Ffh protein.